ANALISIS PEMASARAN CABAI MERAH KERITING DI DESA TAMBARANA KECAMATAN POSO PESISIR UTARA KABUPATEN POSO - Narayan, Sri Laksmi; Hadayani, Hadayani; Khatima, Husnul (Fakultas Pertanian, Universitas Tadulako, 2024)
This study examined the marketing channels, marketing margins, price share received by farmers, and the overall efficiency of marketing curly red chilies (Capsicum annuum) in Tambarana Village, Poso Pesisir Utara Subdistrict, Poso District. The research was conducted between April and May 2021. A census method was used to select farmer respondents, resulting in a sample size of 35 farmers engaged in curly red chili cultivation. Additional respondents, including one collector trader, one retail trader, and two end consumers, were identified through tracing sampling techniques, yielding a total of 39 participants in the study. The analysis revealed that the total marketing margin for Channel I was IDR 10,000.00, while Channel II had a total margin of IDR 9,000.00. The price share received by farmers was 60.0% for Channel I and 62.5% for Channel II. Marketing efficiency was 1.94% for Channel I and 0.90% for Channel II. The identified marketing channels for curly red chilies in Tambarana Village are: (i) Producers → Collectors → Retailers → End Consumers, and (ii) Producers → Collectors → Retailers → End Consumers. Channel II was found to be more efficient, as indicated by its lower total margin and higher price share for farmers. This suggests that Channel II minimizes the price differential between consumer expenditure and producer income, thereby indicating a more equitable distribution of market benefits to the farmers involved.